Digital Smart Marketing: Membangun UMKM Tangguh di Era Ekonomi Digital 5.0 - Enrico Aziezy; Heru Cahyo; Wisnu Wijayanto; Zhika Vilanti; Florenkias Nikosal (Madani : Indonesian Journal of Civil Society, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening the local economy of Sunyalangu Village, Karanglewas District, Banyumas Regency. However, most MSMEs still face limitations in utilizing digital technology, particularly in marketing, business administration, and transaction management. This community service activity, titled "Building Resilient MSMEs in the Digital Economy 5.0 Era," aims to improve  digital literacy and technology-based business management skills among MSMEs. This program was implemented using a gradual training, mentoring, and counseling approach from October to November 2025. A total of 30 MSMEs participated in the activities, which included digital literacy counseling, digital marketing training through social media and marketplaces, and assistance in creating online store accounts and digital-based administration systems. The results of the activity showed that most participants successfully established active marketplace accounts and began implementing online marketing strategies, which have resulted in an expanded market reach and increased business operational efficiency. However, limited internet infrastructure and the availability of digital devices remain obstacles to optimizing technology utilization. Overall, this activity has had a positive impact on changing the business behavior of MSMEs and strengthening their business independence and resilience in the face of the digital economy's development.